Effects of fed mycotoxin contaminated diets supplemented with spray-dried porcine plasma on cholinergic response and behavior in piglets - MÜLLER,LUCIELI K.F. (2019)
Abstract: The aim of this study was to evaluate the effect of spray-dried porcine plasma (SDPP) supplementation on cholinesterase enzymes and its relationship with animal behavior of weaning piglets exposed to mycotoxin contaminated diets. To achieve these objectives, two experimental design approaches were used. Male piglets (7.15±0.61kg) were allocated in four groups: CTL group received a regular diet; SDPP group received a regular diet and 6% SDPP; MYC group received a diet containing desired contamination of 210 µg/kg aflatoxins and 6.690 µg/kg fumonisins; group MYC+SDPP received 253 µg/kg aflatoxins, 6930 µg/kg fumonisins and 6% SDPP. The animals treated with mycotoxin co-contaminated diets showed an increase in AChE and BChE activities in peripheral system (MYC) when compared to control (CTL). Furthermore, supplementation with SDPP (MYC+SDPP group) prevented the mycotoxin-related reduction of AChE in blood and brain. Behavioral tests showed that sleeping and resting behaviors were more often observed in the MYC group; this group also fed fewer times when compared to the other groups, characterizing the deleterious effect of mycotoxins. Taken together, the data suggest changes in AChE and BChE activities may indicate alterations in cholinergic neurotransmission and consequently in the behavior of piglets.